Impact of chronic illness on functional outcomes and quality of life among injured older adults. Issue 9 (September 2021) - Sokas, Claire; Herrera-Escobar, Juan Pablo; Klepp, Timothy; Stanek, Ewelina; Kaafarani, Haytham; Salim, Ali; Nehra, Deepika; Cooper, Zara
Highlights: Almost half of older adults (≥65 years) in a multi-institutional trauma registry had a chronic illness at time of injury. Chronically ill injured older adults have worse functional outcomes and worse physical health-related quality of life 6-12 months post-injury. Despite chronic illness and long-term functional limitations, older adults had preserved mental health when compared to population norms. Understanding the interplay between burden of chronic illness and new injury on quality of life is essential for long-term recovery. Abstract: Introduction: Trauma care for injured older adults is complicated by pre-existing chronic illness. We examined the association between chronic illness and post-injury function, healthcare utilization and quality of life. Methods: Trauma patients ≥65 years with an Injury Severity Score (ISS) ≥9 discharged from one of three level-1 trauma centers were interviewed 6-12 months post-discharge. Patients were asked about new functional limitations, injury-related emergency department (ED) visits or readmission, and health-related quality of life (HRQoL). Trauma registry data was used to determine presence of seven chronic illnesses. Adjusted regression models examined associations between increasing number of chronic illness (0, 1, ≥ 2) and outcomes. Results: Of 1, 379 patients, 46.5% had at least one chronic illness. In adjusted analysis, any chronic illness was associated with higher odds of new functional limitation (1 chronic illness, OR1.54, CI: 1.20-1.97; ≥2, OR1.69, CI: 1.16-2.48) and worse physical health-related QoL (1 chronic illness adj. mean diff= -4.0, CI: -5.6 to -2.5; ≥2 adj. mean diff.= -4.4, CI: -7.3 to -1.4, p<0.01). Mental health post-injury was consistent with population norms across all groups. Conclusion: Presence of any chronic illness in older adults is associated with new functional limitations and worse physical HRQoL post-injury, but unchanged mental health. Focused interventions are needed to support long-term recovery.